IMovie '09 & iDVD for Mac OS X - Carlson, Jeff (Berkeley Peachpit Press, 2009)
This full-color, amply illustrated, accessible book teaches readers the essential skills necessary for creating compelling movies with iMovie '09 and iDVD. Readers can follow the step-by-step instructions from the beginning to get a tour of the applications or look up specific tasks to learn just what they need to know.
Include Index and Illustrations
Keywords: Mac OS